Worlds More or Less: Nineteenth-Century Ethno-Astronomy and Cosmologies of Reference. Issue 5 (2nd November 2021) - Garofalo, Devin M.
ABSTRACT: This essay reads William Herschel's nebular hypothesis (and the debates it galvanized) in light of Sylvia Wynter's account of the cosmology of Man. Tracing the relationship between Western monohumanism and "ethno-astronomy, " Wynter demonstrates how the post-Copernican worldview posited Earth as materially contiguous with the heavens and only one sphere among many. If, as Wynter argues, this rupture facilitated the transhistorical absolutization of Man as the human, the question of form is key to this history. For, insofar as the form of the sphere differentiates world-making Man from merely world-inhabiting Others (both human and nonhuman), it subtends British colonial schemas of empire and race. Nineteenth-century writings about nebulae are curious in this context for how they figure beyond the ethno-astronomy of Man. In attempting to formalize nebulae—gossamer celestial objects that possess no outline—thinkers from Thomas De Quincey to John Pringle Nichol glimpse a cosmos that discomposes the contiguities of both matter and reference upon which the colonial liberal subject's cosmology of whiteness depends. This becomes especially apparent as nebulae turn the workings of analogy haywire. Pushed to the point of failure, analogy inadvertently discerns and asserts a world whose pluriversal configurations of human and nonhuman might inform anti- and decolonial projects.